Prevalence of Asymptomatic Apical Periodontitis and its Association with Coronary Artery Disease in a Brazilian Subpopulation - Bruna Paloma de Oliveira; Andréa Cruz Câmara; Carlos Menezes Aguiar (University of Zagreb. School of Dental Medicine, 2017)
Objective: The aim of the present study was to determine the prevalence of asymptomatic apical periodontitis (AAP) and its association with coronary artery disease (CAD) in a Brazilian subpopulation, and to examine the correlation of AAP with gender, age and most frequently affected dental elements. Methods: The data were collected from medical records of the patients (n = 1346) treated at the Specialization in Endodontics Clinic of the Federal University of Pernambuco in the period between 2003 and 2010. From each patient, the following variables were recorded: gender, age, endodontically compromised teeth, endodontic diseases diagnosed and the history of CAD. The data were analyzed using Pearson's chi-square test adopting a significance level of 5%. Results: AAP was diagnosed in 574 patients (42.6%), corresponding to 641 teeth (40.1%). Both genders (p = 0.082), and all age groups (p = 0.190) were affected similarly. The upper incisors (52.8%, p <0.001) had a higher prevalence of AAP. The patients with AAP showed 1.45 times more chance of exhibiting CAD (p = 0.307). Conclusions: The results pointed out that the prevalence of AAP in this population was high and similar to that observed in other countries. A positive association, but not statistically significant, between AAP and CAD was found.